PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA - Satriadi, Dimas (Jurnal Benefita, 2017)
The problem that occurs is the employee's productivity is not optimal because of the turnover indicated bank last few months either on a permanent employee, daily worker and of apprentices. the purpose of this study was to determine the effect of leadership and motivation to work productivity at Bank BRI Branch Tanjungpinang. In this study will be the population is numbering 50 people.  style of leadership with the highest average grades are in a democratic dimension, which means head of the BRI branch Tanjungpinang have democratic leadership style that is very strong in leading employees who are in their environment. The highest average value of the variable motivation is the dimension of hope, with an average value of 3.93 that is included in the category enough. The highest average value on work productivity variable is the dimension of labor efficiency, with an average value of 4.35 that is included in the very high category.That relationship / correlation between variables Leadership tightly enough (X1), and Motivation (X2) with the Work Productivity in Bank BRI Branch Tanjungpinang of 0.183 or have a direct impact of 18.8%.